Expedient Synthesis of Substituted Benzoheterocycles using 2‐Butoxy‐2, 3‐dihydrofurans as [4+2] Benzannulation Reagents. Issue 14 (9th May 2016) - Liu, Changhui; Huang, Wenbo; Wang, Man; Pan, Bin; Gu, Yanlong
Abstract: 2‐Alkoxy‐2, 3‐dihydrofurans were found to be versatile benzannulation reagents. Indoles can be synthesized in good to excellent yields via the [4+2] annulation of 2‐butoxy‐2, 3‐dihydrofuran with pyrroles catalyzed by copper bromide. With the same protocol, carbazoles can also be obtained when indoles are used as starting material with the aid of p ‐toluenesulfonic acid. This type of benzannulation reagent can also be used to synthesize benzofuran, benzothiophene and naphthalene derivatives in the presence of a catalytic amount of triflic acid in moderate yields. This benzannulation protocol features wide substrate scope and mild reaction condition. Moreover, most of examples have a good regioslectivity. Abstract :